INOVASI PEMBELAJARAN BIOLOGI MELALUI PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS KETERAMPILAN PROSES SAINS UNTUK SMA - B, Nurhayati; Syahirah, St; L, Hamka; Hadis, Abdul (Biosel Biology Science and Education, 2022)
This research is an innovation in biology learning that aims to develop student worksheets based on science process skills, especially on the Human Digestive System material for class XI Senior High School. This research is a type of research and development (R&D) that uses the ADDIE model ((Analyze, Design, Development, Implement, & Evaluate). The products that have been developed are assessed by two expert validators and then practical trials are carried out based on the responses of teachers and students The implementation of the Student Worksheet that has been developed was carried out by means of a limited trial at SMAN 3 Makassar, SMAN 11 Makassar and SMAN 16 Makassar. The data collection technique was carried out through filling out questionnaires for teacher and student responses. The results showed that the student worksheets based on science process skills that have been developed from the validation test results are in the valid category and the practicality test results from the teacher's responses are in the practical category and the student responses are in the very practical category. Therefore research on developing student worksheets based on science process skills this is innovation in Biology learning. The conclusion of this research is that the student worksheets based on high school science process skills that have been developed are declared valid and very practical, and are innovations in Biology learning. Keywords: Student Worksheets, Science Process Skills, Valid, Practical